Pengolahan Sampah Organik Daun Kering menjadi Briket Arang Berteknologi Tepat Guna - Andre Tri Saputra; Muhammad Khoiril Akhyar; Moh Amar Shofyan; Irfan Arviansyah; Chantika Cinta Almira (Universitas Muria Kudus, 2026)
The socialization activity on sorting and processing organic dry leaf waste into charcoal briquettes in Besito Village aims to enhance community awareness of waste management based on appropriate technology. The implementation methods included interactive socialization and direct demonstrations of charcoal briquette production. Participants consisted of the Besito Village Government, Besito Village-Owned Enterprises (BumDes), the general community, members of the Family Welfare Movement (PKK) at the RT level, and the Besito Village Youth Organization (Karang Taruna). The results indicate an improvement in community understanding regarding waste sorting techniques, charcoal briquette processing, and the potential for reducing organic waste volume. The outputs of this program include the formation of an independent briquette production group, technical guidelines, and the utilization of the product as an eco-friendly alternative energy source